2021
DOI: 10.1002/cpt.2352
|View full text |Cite|
|
Sign up to set email alerts
|

Utilizing Large Electronic Medical Record Data Sets to Identify Novel Drug–Gene Interactions for Commonly Used Drugs

Abstract: Real-world prescribing of drugs differs from the experimental systems, physiologicalpharmacokinetic (PK) models and clinical trials used in drug development and licensing, with drugs often used in patients with multiple comorbidities with resultant polypharmacy. The increasing availability of large biobanks linked to electronic healthcare records enables the potential to identify novel drug-gene interactions in large populations of patients. In this study we used 3 Scottish cohorts and UK Biobank to identify d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The most common repurposing target was diabetes-related, consisting of 10 out of the 33 publications 17 , 26 , 29 , 32 , 37 42 , including type 2 diabetes 37 , 41 , 42 , gestational diabetes 17 , diabetes (unspecified) 26 , 29 , diabetes-related tests including glycated hemoglobin 32 and Fasting Blood Glucose 38 – 40 . Six publications did not focus on any specific diseases 21 , 22 , 27 , 28 , 43 , 44 . For example, Dang et al 21 aimed to establish a generic process and method to integrate phenomic data in EHR with omic and drug data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common repurposing target was diabetes-related, consisting of 10 out of the 33 publications 17 , 26 , 29 , 32 , 37 42 , including type 2 diabetes 37 , 41 , 42 , gestational diabetes 17 , diabetes (unspecified) 26 , 29 , diabetes-related tests including glycated hemoglobin 32 and Fasting Blood Glucose 38 – 40 . Six publications did not focus on any specific diseases 21 , 22 , 27 , 28 , 43 , 44 . For example, Dang et al 21 aimed to establish a generic process and method to integrate phenomic data in EHR with omic and drug data.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, others indicated open software, which they used, without their practical implementations 20 , 27 , 45 . Lastly, some of the studies shared the analysis and results in the form of supplements or separated links 19 , 26 , 27 , 31 , 33 , 35 , 36 , 41 , 42 , 44 47 , 49 52 .…”
Section: Resultsmentioning
confidence: 99%
“…19,20 However, such a new pharmacogenetic paradigm has not been exploited in China, in which the LoF variants are carried by around 60% of this ethnic group. 14,21 Here, we leveraged a biobank linked to a Chinese EMR database to ascertain clopidogrel users in the primary care settings. By retrieving EMR information for each individual, their drug exposure and incidence of ischemic stroke over a maximum of a 3-year follow-up period were examined.…”
Section: Articlementioning
confidence: 99%
“…Several studies of this kind have demonstrated biological resources linked to EMR systems are valuable platforms that confirmed about 25% of the White population carrying CYP2C19 LoF variants indeed had a higher risk of stroke upon clopidogrel treatment 19,20 . However, such a new pharmacogenetic paradigm has not been exploited in China, in which the LoF variants are carried by around 60% of this ethnic group 14,21 …”
mentioning
confidence: 99%
“…For example, Malki et al used three Scottish cohorts and the UK Biobank (with linked electronic healthcare records) to identify novel DGIs for 50 most commonly used drugs and 162 variants in 35 genes involved in drug pharmacokinetics. 185 In addition to an efficacy endpoint (systolic blood pressure reduction), they used two phenotypes based on prescribing behaviour (drug-stop and dose-decrease, which are proxies for altered efficacy or tolerability), which enabled them to replicate 11 known DGIs and identify eight novel ones. On the other hand, McInnes and Altman searched the UK Biobank for DGIs among 200 drugs and 9 genes using maintenance dose (the average milligrams of drug per day for the last five prescriptions of each drug) and differential drug response phenotypes (diagnosis codes in primary care data, eg risk of developing a specific side effect).…”
Section: Challenges In Clinical Practicementioning
confidence: 99%